Maladaptive schema modes as the predictor of post-traumatic stress disorder among trauma survivors - Sabir Zaman; kehkashan Arouj; Shahid Irfan; Ishrat Yousaf (Journal of the Pakistan Medical Association, 2021)
Objectives: To study the relationship between dysfunctional schema modes and post-traumatic stress disorder among trauma survivors. Method: A cross-sectional study was conducted in public hospital (Pakistan Institute of Medical Sciences) Islamabad, Pakistan, from March 2019 to August 2019. Two scales were used, Schema Mode Inventory (SMI) for assessment of maladaptive and adaptive schema, whereas, for PTSD assessment, Clinician Administered PTSD Scale (CAPS-5) was used. Total 281 patients of TBI and orthopedic trauma were studied, of which 137 had been diagnosed with orthopedic trauma, 96 were TBI, and 48 had suffered from multiple injuries that were older than 18 years. Result: Simple linear regression showed that maladaptive schema mode was associated with PTSD. Moreover, the result showed that the prevalence of PTSD severity symptoms were greater in survivors with maladaptive than adaptive schema modes. Further result showed that PTSD Symptoms and dysfunctional schema modes were higher in moderate injured patient’s M (42.14) SD (7.36). In the same way, intentionally injured patient’s M (42.70) SD (6.92) and female trauma survivor’s M (42.05) SD (8.26) had higher PTSD symptoms. Conclusion: The findings of this study demonstrates that maladaptive schema mode leads to PTSD symptoms among trauma survivors with history of orthopedic injury, TBI and multiple injury patients. Keywords: PTSD Symptoms, Maladaptive Schema Modes, Continuous....